Genome-wide DNA methylation analysis pre- and post-lenalidomide treatment in patients with myelodysplastic syndrome with isolated deletion (5q) - Hecht, Anna; Meyer, Julia A.; Jann, Johann-Christoph; Sockel, Katja; Giagounidis, Aristoteles; Götze, Katharina S.; Letsch, Anne; Haase, Detlef; Schlenk, Richard Friedrich; Haferlach, Torsten; Schafhausen, Philippe; Bug, Gesine; et al. (Annals of hematology, 2021)
Myelodysplastic syndrome (MDS) with isolated deletion of chromosome 5q (MDS del5q) is a distinct subtype of MDS with quite favorable prognosis and excellent response to treatment with lenalidomide. Still, a relevant percentage of patients do not respond to lenalidomide and even experience progression to acute myeloid leukemia (AML). In this study, we aimed to investigate whether global DNA methylation patterns could predict response to lenalidomide. Genome-wide DNA methylation analysis using Illumina 450k methylation arrays was performed on n=51 patients with MDS del5q who were uniformly treated with lenalidomide in a prospective multicenter trial of the German MDS study group. To study potential direct effects of lenalidomide on DNA methylation, 17 paired samples pre- and post-treatment were analyzed. Our results revealed no relevant effect of lenalidomide on methylation status. Furthermore, methylation patterns prior to therapy could not predict lenalidomide response. However, methylation clustering identified a group of patients with a trend towards inferior overall survival. These patients showed hypermethylation of several interesting target genes, including genes of relevant signaling pathways, potentially indicating the evaluation of novel therapeutic targets.
Gesehen am 26.08.2021